Inovasi Perkebunan Rumah Pangan untuk Meningkatkan Kesehatan Masyarakat - Ria Mardiana; Solfema Solfema; Lili Dasa Putri (Universitas Palangka Raya, 2025)
The innovation of home food gardening aims to improve public health by providing access to healthy, nutritious, and diverse food independently. The background of this article is the need for sustainable solutions to address malnutrition, dependency on chemically-treated food, and low public awareness of healthy living habits. This article employs a literature review method to analyze various relevant sources regarding the role of home food gardens in supporting community health. The discussion focuses on the benefits of home food gardening in providing organic food, reducing household expenses, and raising awareness of healthy lifestyle practices. The findings reveal that this innovation enhances access to nutritious food, improves environmental quality, and empowers communities sustainably. Thus, home food gardening serves as an effective strategy to improve public health across different regions.